Sand accumulation in the digestive tract of rabbits (Oryctolagus cuniculus) and guinea pigs (Cavia porcellus): The role of the appendix. (29th October 2021) - Winter, Nicole; Clauss, Marcus; Codron, Daryl; Hummel, Jürgen; Müller, Jaqueline; Richter, Henning; Kircher, Patrick; Hatt, Jean‐Michel; Martin, Louise Françoise
Abstract: We determined location and amount of accumulated sand in the gastrointestinal tract (GIT) of rabbits ( Oryctolagus cuniculus ) and guinea pigs ( Cavia porcellus ) fed diets containing external (silicate) abrasives. Computed tomographic abdominal images of rabbits (n = 44) and guinea pigs (n = 16) that each received varying numbers (4–7) of different diets for 14 days each (total n = 311 computed tomographs), and radiographs of dissected GIT and presence of silica in GIT content (n = 46 animals) were evaluated. In rabbits, the majority of accumulated sand was located in the caecal appendix, an elongated, intestinal structure in the left side of the abdomen. The 'wash‐back' colonic separation mechanism in rabbits may be partly responsible for a retrograde transport of sand back to the caecum, where dense, small particles accumulate in the appendix. The appendix likely acted as a reservoir of these particles, leading to significant effects not only of the momentary but also of the previous diet on recorded sand volumes in the rabbits. Guinea pigs have no caecal appendix and a colonic separation mechanism not based on a 'wash‐back'. Less sand accumulation was found in their GIT without a specific location pattern, and there were less previous diet effects in this species. None of the rabbits or guinea pigs developed clinical signs of obstruction during the study, and the recorded sand volumes represented 1.0 ± 1.2% of the 14‐d sand intake in rabbits and 0.2 ± 0.2% in guinea pigs. Accumulation of sand in volumes up to 10 cm 3 in the GIT of rabbits does not seem to cause clinical health impairment. Large inter‐individual differences in rabbits indicate inter‐individual variation in proneness to sand accumulation. The reason for the presence of a sand‐trapping caecal appendix in animals that are, due to their burrowing lifestyle and feeding close to the ground, predestined for accidental sand ingestion, remains to be unveiled. Abstract : Serial dorsoventral abdominal CT images of rabbits fed different amounts of sand as part of a serial feeding experiment. Given images are from different individuals in order to create an impression of the reproducibility of the sand's position in the abdomen. Sand accumulation is visible as strong radiodense (white) matter (indicated by yellow arrows) lying always on the left side of the abdomen in the tip of the caecal appendix. St stomach, CE caecum.